ZAR1 and ZAR2 are required for oocyte meiotic maturation by regulating the maternal transcriptome and mRNA translational activation. Issue 21 (10th October 2019) - Rong, Yan; Ji, Shu-Yan; Zhu, Ye-Zhang; Wu, Yun-Wen; Shen, Li; Fan, Heng-Yu
Abstract: Zar1 was one of the earliest mammalian maternal-effect genes to be identified. Embryos derived from Zar1 -null female mice are blocked before zygotic genome activation; however, the underlying mechanism remains unclear. By knocking out Zar1 and its homolog Zar2 in mice, we revealed a novel function of these genes in oocyte meiotic maturation. Zar1/2 -deleted oocytes displayed delayed meiotic resumption and polar body-1 emission and a higher incidence of abnormal meiotic spindle formation and chromosome aneuploidy. The grown oocytes of Zar1/2 -null mice contained decreased levels of many maternal mRNAs and displayed a reduced level of protein synthesis. Key maturation-associated changes failed to occur in the Zar1/2 -null oocytes, including the translational activation of maternal mRNAs encoding the cell-cycle proteins cyclin B1 and WEE2, as well as maternal-to-zygotic transition (MZT) licensing factor BTG4. Consequently, maternal mRNA decay was impaired and MZT was abolished. ZAR1/2 bound mRNAs to regulate the translational activity of their 3′-UTRs and interacted with other oocyte proteins, including mRNA-stabilizing protein MSY2 and cytoplasmic lattice components. These results countered the traditional view that ZAR1 only functions after fertilization and highlight a previously unrecognized role of ZAR1/2 in regulating the maternal transcriptome and translational activation in maturing oocytes.